Circulation of Security Models in Southern African Cities: Between Neoliberal Encroachment and Local Power Dynamics - (:unkn) unknown (My University, 2012)
This symposium focuses on the circulation of security governance models in cities of Southern Africa (Johannesburg, Cape Town, Windhoek and Maputo). It consists of three articles analysing at different scales (regional, national and intra‐urban) the circulation of specific neighbourhood‐based solutions to security issues, such as road closures, gated residential developments and business improvement districts. This spreading process, with the South African case at its core, is analysed within the theoretical framework of neoliberalism. The symposium, via this discussion of security models and the way they reflect the changing relationships between state and private actors locally, discusses the relevance of this framework to a fuller understanding of the transformation of Southern African cities.
Keywords: African Research